Motion Graphic: Design for Biology Learning Coordination System to Improve High Order Thinking Skills (HOTS) - Zulfarina Zulfarina*; Molandia Widi Agustin; Nursal Nursal; Yustina Yustina (Universitas Syiah Kuala, 2022)
In order to improve the quality of the learning process and improve high order thinking skills (HOTS), education is required to continue to develop. One of the tools for the learning process and a solution for education is by using the media. Adobe After Effects-based motion graphics media can be used by teachers in the learning process. This study aims to develop and produce Motion Graphic media based on Adobe After Effects in an effort to improve High order thinking skills (HOTS) during the pandemic. The research consists of 3 stages, namely analysis, design and development. Methode of research is Research and Development (RD), using the ADDIE Model. The analysis phase is carried out by observation and interviews using a google form questionnaire and the design and development phase is carried out by utilizing various software. The results of the analysis phase of the study showed that 64.3% of students thought that the material for the coordination system was difficult to understand. The design stage begins with making a storyboard in accordance with the curriculum of 2013 and indicators of student achievement in the coordination system material, followed by making Motion Graphic Video using Adobe Effects software in accordance with the storyboard that has been made. The media generated from this research can be developed and tested further.